2010
DOI: 10.1097/rct.0b013e3181cfc676
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Uterine Endometrial Stromal Sarcoma

Abstract: We demonstrated 2 cases of uterine endometrial stromal sarcoma with emphasis on diffusion-weighted imaging. The tumors showed high signal intensity, and their tumor venous thrombi were clearly depicted on diffusion-weighted imaging. Diffusion-weighted imaging is a useful method not only for diagnosis of endometrial stromal sarcoma but also for preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…19,20 Pathological studies showed a more commonly degenerative change in HGESS than in LGESS. 1,3,4 In our series, degenerative changes were observed in 7 of 13 LGESSs, whereas those changes were observed in both of the 2 HGESSs. Sometimes, the findings of LGESS may mimic a uterine leiomyoma with cystic degeneration 19 ; however, our study showed that the cystic degeneration radially distributed from the central part of the mass to the periphery in 3 LGESSs, which were also a characteristic feature.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…19,20 Pathological studies showed a more commonly degenerative change in HGESS than in LGESS. 1,3,4 In our series, degenerative changes were observed in 7 of 13 LGESSs, whereas those changes were observed in both of the 2 HGESSs. Sometimes, the findings of LGESS may mimic a uterine leiomyoma with cystic degeneration 19 ; however, our study showed that the cystic degeneration radially distributed from the central part of the mass to the periphery in 3 LGESSs, which were also a characteristic feature.…”
Section: Discussioncontrasting
confidence: 39%
“…The cystic, hemorrhagic, and necrotic degenerations were observed in 7 of 13 LGESSs and in both of the 2 HGESSs. Microscopically, LGESSs typically showed small, uniform cells with a round to fusiform nucleus, prominent spiral arteriole-like vessels, a lack of cytological atypia, and a rare mitotic activity (G5 mitotic figures/10 highpower fields), whereas HGESS was characterized by larger, round cells, a prominent thin-walled capillary network, and increasing mitotic activity (910 mitotic figures/10 high-power fields) (Figs.…”
Section: Histopathologic Findings Of Esssmentioning
confidence: 92%
See 2 more Smart Citations
“…Another finding is the continuous extension of the lesion into the adjacent structures along the fallopian tubes, uterine ligaments, or ovaries (120). DWI can visualize this characteristic quite clearly due to the high signal intensity of the tumor (121). An excellent tissue contrast of DWI may facilitate the detection of the detailed tumor extension (121) (Fig.…”
Section: Role Of Mri In Decision Makingmentioning
confidence: 99%